Johannes Reinke: Leben und Werk eines lutherischen Botanikers - Wissemann, Volker (Religion, Theologie und Naturwissenschaft / Religion, Theology, and Natural Science (RThN) - Band 026, 2012)
Includes bibliographical references and indexes